A política de assistência ao educando do IFMA: uma avaliação política da política - Martins, Luciana Paula de Freitas Coêlho (2017)
Political Evaluation of the Education Policy of the Federal Institute of Education, Science and Technology of Maranhão. It analyzes the foundations, conceptions and principles that underlie this policy as well as its relationship with the main national and local programs and legislations dealing with student assistance. The Public Policy of Student Assistance aims to guarantee the access, permanence and completion of the students enrolled in the courses offered in federal educational institutions, with a view to social inclusion, expanded training, knowledge production, improvement of academic performance and quality of life. At IFMA, this policy is designed to meet the demands placed by the students, based on the intervention actions pointed out by the National Student Assistance Program of 2010. It was designed by the formulators so that implementers, managers, teachers and students had a referential for adoption and construction of actions in the field of student assistance. For a critical approach to this policy, this work starts from an analysis of education policy within the capitalist context under the neoliberal aegis, in order to observe how the present stage of technical and ideological development of the system influences the form and structure of the educational policies adopted in Brazil. In addition, it seeks to establish a communication between social assistance, student and educational policies, understood as social policies that are part of the Brazilian social protection system, which tend, in the current conjuncture, to restrict and focus neoliberal policies. The antecedents of the EAP within the IFMA and its formulation process are presented and discussed. It analyzes the foundations, the guiding concept and the principles that sustain PAE-IFMA from the thematic axes: democratization, social inclusion, citizenship, humanistic orientation, transparency and gratuity. Finally, it is verified how the policy of student assistance of the IFMA is organized to attend students of PROEJA in view of their particularities. It is then considered that the PAE-IFMA was boosted by the national context and by determinants of internal order to the institution. It represents a great step in the institutionalization of student assistance actions. It is still an important instrument for student’s access and permanence, although the study revealed some weaknesses and limitations in relation to the achievement of the proposed objectives.